Comparing the accuracy of obstetric sonography and fetal echocardiography during pediatric cardiology consultation in the prenatal diagnosis of congenital heart disease. Issue 2 (10th November 2015) - Lai, Carman Wing Sze; Chau, Adolphus Kai Tung; Lee, Chin Peng
Abstract: Aim: The diagnostic accuracy of fetal echocardiogram performed by an obstetrician alone and that performed jointly by an obstetrician and pediatric cardiologist for congenital heart disease were compared. Materials and Methods: All cases of suspected fetal congenital heart disease (CHD) referred to the Prenatal Diagnostic Clinic at Tsan Yuk Hospital, Hong Kong during 2006–2011 were reviewed. Prenatal fetal echocardiogram findings were compared with postnatal diagnosis. Cases of incorrect prenatal diagnosis with significant difference in prognosis were analyzed qualitatively. Results: One hundred and eleven cases of fetal CHD were analyzed. Complete agreement between prenatal and postnatal diagnosis of CHD was observed in 69.4% of cases by fetal echocardiogram performed by obstetrician and 83.8% by fetal echocardiogram performed during pediatric cardiology consultation ( P = 0.001). Collaboration with a pediatric cardiologist also improved detection of ductal‐dependent cardiac lesions (77.4% vs 86%, P = <0.001). Five cases with an incorrect diagnosis were associated with a different prognosis. Three of the cases involved outflow tract abnormalities with incorrect identification of outflow vessels. Conclusion: Collaboration with a pediatric cardiologist can significantly improve the accuracy of prenatal diagnosis of CHD. In particular, joint consultation is associated with significantly better detection of ductal‐dependent lesions. Outflow tract abnormalities remain a diagnostic challenge in prenatal diagnosis. Incorrect identification of outflow tract vessels was the major cause of incorrect diagnosis in our series.